Tinjauan Filosofis Terhadap Undang-undang Nomor 41 Tahun 2004 Tentang Wakaf - Nor Mohammad Abdoeh (Jurnal Iqtisad, 2020)
Abstract Waqf is the teachings of Islam that purpose to realize prosperity and perpetual endowment property in the context of the interests of worship. Indonesia as the country with the largest Muslim majority in the world has serious attention to the management of waqf, this is proven by the enactment of Law No. 41 of 2004. The purpose of this paper is to know the nature and substance of the regulation. This study uses a philosophical approach by explaining the nature of its formal objects. The conclusion of this paper is that the essence of this regulation is none other than to accommodate the Wakif and Nadzir for the welfare of the community.